Sustainable forest genetic resources programmes in the Newly Independent States of the former USSR: Proceedings of a Workshop 23-26 September 1996, Belovezha, Belarus - Goncharenko, G.G.; Gomel Turok, J.; Gass, T.; Paule, L.; International Plant Genetic Resources Institute (1999)
This workshop was a first opportunity to meet and renew collaboration in forest genetic resources, since the dissolution of the USSR, and it benefited greatly from the expertise and the long tradition of cooperation among the participants and their institutions, which goes back to the beginning of the 1990's. The objectives were to provide an overview of the current activities, to reassess needs and priorities, and to emphasize the interest and capacities of the Newly Independent States to be proactive in international cooperation.